2016
DOI: 10.1111/1365-2745.12613
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration: an overlooked aspect of trait‐based plant community assembly models

Abstract: 1. Despite the disproportionate influence that propagule production, dispersal, seed-to-seedling recruitment and vegetative reproduction can have on plant population and community dynamics, progress has been slow in the directed collection of regeneration traits to inform community assembly outcomes. 2. While seed mass is globally available and linked to growth and reproductive output, there are limits to its explanatory ability. In this essay, we call for expanded efforts to integrate a more diverse set of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
164
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 142 publications
(207 reference statements)
5
164
0
5
Order By: Relevance
“…Few studies so far have incorporated functional traits of early-stage development plant organisms (e.g. saplings) into community assembly models (Larson and Funk, 2016). Specifically, we found that woody species partitioned fine-scale gradients in light availability based on their LMA, and this niche partitioning potentially facilitates species coexistence at the within-community level.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Few studies so far have incorporated functional traits of early-stage development plant organisms (e.g. saplings) into community assembly models (Larson and Funk, 2016). Specifically, we found that woody species partitioned fine-scale gradients in light availability based on their LMA, and this niche partitioning potentially facilitates species coexistence at the within-community level.…”
Section: Discussionmentioning
confidence: 71%
“…This finding provides evidence of trait-based partitioning of fine-scale light availability by woody species at the regeneration level. We also propose that the concept of resource-use strategy successfully applied to adults can be used to define the regeneration niche of plant species (see Larson and Funk, 2016). This trait-based niche partitioning of fine-scale light availability was not evident in the Mediterranean forest community we studied, where light is not expected to be limiting.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Jiménez‐Alfaro et al . ; Larson & Funk ) in favour of functional traits measured solely for the mature plant and, more rarely, also for seedlings. One key seed trait that plays an important role in the regeneration ecology of a species is the ability of the seed to survive desiccation (Tweddle et al .…”
Section: Introductionmentioning
confidence: 99%
“…Plant species may be particularly sensitive to environmental filtering at the regeneration stage and this might be more important than other life‐history stages as species could be totally excluded from a habitat due to inappropriate environmental conditions for germination or successful establishment (Grubb, ). However, our knowledge of plant trait ecology is largely focused on few traits concerning aboveground vegetative growth and morphology, and very few studies have assessed the potential role of regeneration traits (Jiménez‐Alfaro, Silveira, Fidelis, Poschlod, & Commander, ; Larson & Funk, ; Poschlod et al., ; Saatkamp et al., ). Regeneration traits have been long acknowledged as relevant to the natural maintenance of biodiversity (Grubb, ), and have been found to be important for both species coexistence and species sorting (Bernard‐Verdier et al., ; Fernández‐Pascual, Pérez‐Arcoiza, Prieto, & Díaz, ; Pierce, Bottinelli, Bassani, Ceriani, & Cerabolini, ).…”
Section: Introductionmentioning
confidence: 99%